Salinity induced stress in wheat - Ilyas, Mahnoor; Ahad, Arzoo; Batool, Tuba Sharf; Jabbar, Warda; Ejaz, Mahnoor; Gul, Alvina; Ozturk, Munir (Journal of Cereal Research, 2022)
Wheat is the major cereal crop confronting serious abiotic factors that pose an alarming situation regarding its global biomass production and distribution. Salinization is one of those ecological stresses that impair its growth and developmental processes thereby decreasing the crop production. Nearly twenty percent agricultural land encompasses high salt concentration, moreover due to global warming even more arable land is under salinization. Different management solutions have recently been proposed to reduce the negative impacts of salt stress and optimize wheat productivity and nutritional content. This review emphasis on the physio-chemical alterations in wheat under salinity. The reported data revealed that salinity negatively affect multiple processes in wheat during its germination, growth, and maturity. Various adaptive mechanisms to salt stress at the cellular, metabolic, and molecular phases, while the processes governing salinity tolerance remain unknown. Therefore, studying the salt-induced injury and approaches for boosting salt tolerance in wheat is crucial